Evaluation of Smart Portable Device for Food Diagnostics: A Preliminary Study on Cape Hake Fillets (M. capensis and M. paradoxus). (12th February 2019) - Castrica, Marta; Panseri, Sara; Siletti, Elena; Borgonovo, Federica; Chiesa, Luca; Balzaretti, Claudia M.
Abstract : The new smartphone-based food diagnostic technologies offer significant advantages over traditional methods as they can be easily applied in various steps of the agrifood supply chain including household use and also in the food recovery field for charitable purposes, aimed at helping to reduce food waste. Further advantages include the low cost, the minimal equipment, and nonspecialized personnel required. This study evaluated the performance of two instrumental measurements of the sensors: an electronic nose (PEN3; WinMuster Airsense Analytics) and a smart portable device (FOODsniffer; ARS LAB US). The preliminary study was conducted on cape hake fillets. In order to test the performance of PEN3 and FOODsniffer, total volatile basic nitrogen (TVB-N) values were considered as the reference. Principal component analysis (PCA) and Pearson's correlation were performed in order to compare PEN3 with TVB-N, and for the FOODsniffer evaluation, a one-way ANOVA was carried out. A significant correlation was shown between PEN3, first component, and TVB-N ( r  = 0.92, P = 0.01 ). The ANOVA results also confirmed a good agreement between FOODsniffer, TVB-N ( F  = 519.9, P = 0.01 ), and PEN3 ( F  = 143.17, P = 0.01 ). Our simulation results confirmed good performance in both methods.